PENGARUH MANAJEMEN MUTU TERPADU DAN MANAJEMEN RANTAI PASOKAN TERHADAP KINERJA OPERASIONAL PT. BERKAT JAYA MAKMUR ABADI - Mario Yehezkiel Regar; Wiwik Rachmarwi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to analyze and determine the effect of total quality management and supply chain management on operational performance. The sample used a non-probability sampling method, and the data collected was obtained by means of a questionnaire. It was then analyzed using a quantitative method. The results showed that, together, total quality management and supply chain management have a partial and simultaneous effect on operational performance at PT. Berkat Jaya Makmur Abadi.